An investigation on the use of computer to learn english language vocabulary: a case study of form four students in a sub-urban school in Kuching, Sarawak - Mohd Zain, Mazira (2006)
This study was carried out to investigate the benefits of using computer in suburban secondary school in Kuching, Sarawak. The main focuses in this study include three aspects namely, the attitudes, motivation and the performance towards the use of computer to learn English language vocabulary. This study was conducted on 50 respondents who are form four student in a secondary school in Kuching, Sarawak. The instruments used in this research are vocabulary test and questionnaires. Overall, the results of this study showed that students have good attitude and were very motivated to learn English language vocabulary using computer. They have shown their confidence and are motivated to learn English language vocabulary as they have basic computer knowledge. The good performance could be measured after analysing and comparing their results in the pre-test and post-test. They have shown better results in the post-test compared with the pre test after being exposed to the computer program. Based on this study, it can be said that firstly, using computer to learn English language vocabulary is very beneficial and created self-confidence and motivated students. Secondly, students have positive attitudes and motivation towards the use of computer to learn English language vocabulary and can improve their performance in English Language. Thirdly, students have exposure with the interactive computer program. These program have encouraged them to learn English language vocabulary effectively as compared to before being exposed to them.